EKSPLORASI BIDANG-BIDANG PENTING DALAM ILMU KOMUNIKASI DAN PENGABDIAN MASYARAKAT - Wijayanti, Astuti (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This discussion explores the contribution of communication science literature to the understanding of corporate culture, advertising, and socio-humanities aspects in the context of community development. In corporate culture analysis, communication science literature highlights organizational identity, company values, and how communication influences the formation of corporate image. This understanding forms the basis for a cohesive organizational communications strategy and a strong corporate culture. In advertising, communication science literature provides insight into consumer psychology, brand image formation, and the impact of advertising on purchasing behavior. Ethical aspects in advertising are also under the spotlight, creating the basis for effective and responsible campaigns. Socio-humanities aspects in communication science literature discuss the role of communication in social change and community development. This literature provides a deep understanding of how communication can be used to stimulate positive change and build sustainability in community development projects. The importance of collaboration between academics and practitioners in integrating the findings of the science communication literature into practical contexts is also highlighted. Conclusions and suggestions highlight the need to apply literature findings in organizational communication strategies and community service, as well as the importance of openness to the latest developments in communication science literature.